Clinical features and therapeutic responses to proton pump inhibitor in patients with severe reflux esophagitis: A multicenter prospective observational study. Issue 1 (8th December 2020) - Isshi, Kimio; Matsuhashi, Nobuyuki; Joh, Takashi; Higuchi, Kazuhide; Iwakiri, Katsuhiko; Kamiya, Takeshi; Manabe, Noriaki; Nakada, Tatsuya; Ogawa, Maiko; Arihiro, Seiji; Haruma, Ken; Nakada, Koji
Abstract: Background and Aim: In patients with severe erosive reflux disease (ERD; Los Angeles classification grade C/D) who do not undergo endoscopic examination, insufficient strength and duration of proton pump inhibitor (PPI) therapy may lead to complications such as esophageal bleeding and stenosis. Therefore, to provide a safe and effective treatment for gastroesophageal reflux disease (GERD), we investigated the clinical features of patients with severe ERD and their responses to PPI therapy. Methods: Patients with GERD symptoms received PPI therapy for 4 weeks after endoscopic examination. The patients completed the Gastroesophageal reflux and dyspepsia therapeutic efficacy and satisfaction test questionnaire before and 2 or 4 weeks after PPI treatment. Patient characteristics, presence/absence of coexisting atrophic gastritis (AG) and hiatus hernia (HH), and responses to PPI therapy were compared in patients with GERD among three groups (nonerosive reflux disease, mild ERD [grade A/B], and severe ERD). Results: The severe ERD group had a significantly higher proportion of males, higher body mass index, and longer duration of GERD morbidity. Furthermore, the severe ERD group also had a significantly lower incidence of coexisting AG and higher incidence of HH. There was no difference in the severity of GERD before PPI treatment among the three groups. Unexpectedly, the response to PPI therapy was the best in the severe ERD group. Conclusion: Sufficient strength and period of PPI therapy are required, even if the symptoms show early improvement, when treating GERD patients without performing endoscopy, considering the possibility of severe ERD. Abstract : Outpatients with symptomatic gastroesophageal reflux disease (GERD) who will be prescribed proton pump inhibitor (PPI) treatment were recruited for this study. The patient characteristics, presence/absence of coexisting atrophic gastritis (AG) and hiatus hernia (HH), and responses to PPI therapy were compared in the patients with GERD, divided into three groups (nonerosive reflux disease, mild erosive reflux disease (ERD), and severe ERD). The severe ERD group also had a significantly lower incidence of coexisting AG and higher incidence of HH. There was no difference in the severity of the GERD symptoms before PPI treatment among the three groups. Unexpectedly, severe ERD patients had the greatest PPI treatment effect among the three groups.